Intrapartum Basal Ganglia–Thalamic Pattern Injury and Radiologically Termed “Acute Profound Hypoxic–Ischemic Brain Injury” Are Not Synonymous - Smith, Johan; Solomons, Regan; Vollmer, Lindi; Langenegger, Eduard J.; Lotz, Jan W.; Andronikou, Savvas; Anthony, John; van Toorn, Ronald (American Journal of Perinatology, 2020)
Objective Human cases of acute profound hypoxic-ischemic (HI) injury (HII), in which the insult duration timed with precision had been identified, remains rare, and there is often uncertainty of the prior state of fetal health.Study Design A retrospective analysis of 10 medicolegal cases of neonatal encephalopathy-cerebral palsy survivors who sustained intrapartum HI basal ganglia-thalamic (BGT) pattern injury in the absence of an obstetric sentinel event.Results Cardiotocography (CTG) admission status was reassuring in six and suspicious in four of the cases. The median time from assessment by admission CTG or auscultation to birth was 687.5 minutes (interquartile range [IQR]: 373.5–817.5 minutes), while the median time interval between first pathological CTG and delivery of the infant was 179 minutes (IQR: 137–199.25 minutes). The mode of delivery in the majority of infants (60%) was by unassisted vaginal birth; four were delivered by delayed caesarean section. The median (IQR) interval between the decision to perform a caesarean section and delivery was 169 minutes (range: 124–192.5 minutes).Conclusion The study shows that if a nonreassuring fetal status develops during labor and is prolonged, a BGT pattern HI injury may result, in the absence of a perinatal sentinel event. Intrapartum BGT pattern injury and radiologically termed “acute profound HI brain injury” are not necessarily synonymous. A visualized magnetic resonance imaging (MRI) pattern should preferably solely reflect the patterns description and severity, rather than a causative mechanism of injury.Key Points
Keywords: hypoxic–ischemic encephalopathy; acute profound; basal ganglia thalamus injury pattern; cerebral palsy